Analisis Pengendalian Persediaan Bahan Baku dengan Menggunakan Metode EOQ pada PT Sigma Indonesia MFG - Elsa Fitriyani; Matdio Siahaan (Neolectura, 2020)
The aim of this research is to find out whether the control of raw material inventory at PT Sigma Indonesia Manufacturing is efficient or not. The main raw material used by PT Sigma Indonesia Manufacturing is 8.0 diameter STKM material. PT Sigma Indonesia Manufacturing processes the STKM diameter 8.0 material into finished goods, namely Collar 8.0. Problems faced by companies in relation to raw material supplies include the optimal purchase of raw materials, safety supplies, and the total cost of raw material supplies. To answer the existing problems, the author uses the EOQ (Economical Order Quantity) method. This analysis consists of the optimal purchase of raw materials, safety stock, and Total Inventory Cost. The calculation of optimal raw material purchases uses the EOQ (Economical Order Quantity) method, the calculation of safety stock is calculated using a standard deviation while the Total Inventory Cost is calculated using Microsoft Excel. The data used are data on the purchase and use of Collar 8.0 raw materials during the period January 2016 to December 2018. The results obtained after EOQ calculations are the amount of economical raw materials for each purchase in 2016 amounted to 278 sticks, 2017 totaled 284 sticks, 2018 a total of 285 cigarettes. Total Inventory Cost according to the EOQ calculation in 2016 amounted to Rp165,591, in 2017 amounted to Rp168.754, in 2018 amounted to Rp169.325. Total Inventory Cost incurred by the company in 2016 was Rp215.268, 2017 amounted to Rp219.380 , in 2018 amounting to Rp220.122.